2019
DOI: 10.1186/s12913-019-4345-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare middle managers’ experiences of developing capacity and capability: a systematic review and meta-synthesis

Abstract: Background Healthcare middle managers play a central role in reducing harm, improving patient safety, and strengthening the quality of healthcare. The aim of this systematic review was to identify the present knowledge and critically discuss how healthcare middle managers experienced to develop the capacity and capability for leadership in a healthcare system characterized by high complexity. Methods This comprehensive systematic review provided evidence of healthcare m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Several studies report that employees show restraint and consider the QI work to be useless if they feel forced to take part in it [2,4,9,21]. Other studies confirm that positive relationships and aligning QI work with professional logic [22], in conjunction with work structures that empower employees [13], influence how employees engage in QI work. The supervision and learning methods inspired by Illeris' [24] perspective of transformative learning, which involves changes in the learners' perspectives as a result of critical reflection and open discourse, might have been an effective contribution to back up the leaders and give them a new understanding in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report that employees show restraint and consider the QI work to be useless if they feel forced to take part in it [2,4,9,21]. Other studies confirm that positive relationships and aligning QI work with professional logic [22], in conjunction with work structures that empower employees [13], influence how employees engage in QI work. The supervision and learning methods inspired by Illeris' [24] perspective of transformative learning, which involves changes in the learners' perspectives as a result of critical reflection and open discourse, might have been an effective contribution to back up the leaders and give them a new understanding in practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that a comprehensive network of processes is needed to support the continuing development in nursing leadership, and is best suited to take place within the organization [12]. Studies show that FLNMs who play an essential role in quality management need contextual support to develop the capacity and capability for leadership [13]. Promoting a supportive working atmosphere can contribute to professional networking and collaboration, where FLNMs feel free to share their vision and purpose, thereby developing decision-making, managerial, and leadership abilities [14].…”
Section: Nursing Leadership Developmentmentioning
confidence: 99%
“…The members of top management were experienced to value economic reporting and budgetary control. Previous research shows how HMMs’ development of capacity and capability for leadership should be supported by bottom-up processes, interactions within networks and an empowering upper management (Hartviksen et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…HMMs’ development of capacity and capability for leadership have been identified as part of a bottom-up development process that involves building self-confidence, knowledge, skills and tools. This process was facilitated by interaction in networks and an empowering approach from upper management (Hartviksen et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation